Application of Dynamic Systems Development Method in WEB-Based Promotion Media - Chandra Putra Dinata; Yulvia Nora Marlim (Institut Bisnis dan Teknologi Pelita Indonesia, 2020)
Various kinds of promotional media such as billboard rental, newspapers and television. The promotion has a good impact, but it is quite expensive. In this developing era, it is online media that is most in demand by many people because of its practical nature. Web-based promotional media is a web which specifically becomes a place to promote information such as coupons and discounts that exist and gather people who want to promote in a practical way, so as to save money and also time in the process of making promotions. Dynamic System Development Method (DSDM) is a system framework that provides a lot of knowledge about project management. The DSDM method framework has five stages in designing and building the system, namely the feasibility stage, business studies, functional model iteration, design and build iteration, and implementation phase. The use of DSDM in system development can save time because the system design process is structured and neat, and also after the system is successfully built, the system maintenance process using the DSDM method can be done quickly and efficiently. The system to be built also uses a Codeigniter software framework. The Codeigniter framework is a PHP framework that can save time for programmers in designing a system.